Defense Enzyme Responses in Dormant Wild Oat and Wheat Caryopses Challenged with a Seed Decay Pathogen - Fuerst, E. Patrick; James, Matthew S.; Pollard, Anne T.; Okubara, Patricia A. (Frontiers in Plant Science, 2018)
Seeds have well-established passive physical and chemical defense mechanisms that protect their food reserves from decay-inducing organisms and herbivores. However, there are few studies evaluating potential biochemical defenses of dormant seeds against pathogens. Caryopsis decay by the pathogenic Fusarium avenaceum strain F.a.1 was relatively rapid in wild oat (Avena fatua L.) isoline ‘M73’, with >5 0% decay after 8 days with almost no decay in wheat (Triticum aestivum L.) var. RL4137. Thus, this fungal strain has potential for selective decay of wild oat relative to wheat. To study defense enzyme activities, wild oat and wheat caryopses were incubated with F.a.1 for 2-3 days. Whole caryopses were incubated in assay reagents to measure extrinsic defense enzyme activities. Polyphenol oxidase, exochitinase, and peroxidase were induced in whole caryopses, but oxalate oxidase was reduced, in response to F.a.1 in both species. To evaluate whether defense enzyme activities were released from the caryopsis surface, caryopses were washed with buffer and enzyme activity was measured in the leachate. Significant activities of polyphenol oxidase, exochitinase, and peroxidase, but not oxalate oxidase, were leached from caryopses. Defense enzyme responses were qualitatively similar in the wild oat and wheat genotypes evaluated. Although the absolute enzyme activities were generally greater in whole caryopses than in leachates, the relative degree of induction of polyphenol oxidase, exochitinase, and peroxidase by F.a.1 was greater in caryopsis leachates, indicating that a disproportionate quantity of the induced activity was released into the environment from the caryopsis surface, consistent with their assumed role in defense. It is unlikely that the specific defense enzymes studied here play a key role in the differential susceptibility to decay by F.a.1 in these two genotypes since defense enzyme activities were greater in the more susceptible wild oat, compared to wheat. Results are consistent with the hypotheses that (1) dormant seeds are capable of mounting complex responses to pathogens, (2) a diversity of defense enzymes are involved in responses in multiple plant species, and (3) it is possible to identify fungi capable of selective decay of weed seeds without damaging crop seeds, a concept that may be applicable to weed